PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING PADA MATA PELAJARAN OTOMATISASI TATA KELOLA SARANA DAN PRASARANA KELAS XI SMK NEGERI 1 PANGKALANBARU - Septi Wuri Handayani; Muhammad Sholeh Marsudi (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
One of the objectives of the Office Governance Automation skill competency is to create a workforce who is able to apply their knowledge and skills in the field of office administration automation. Learning in productive subjects is not only conveying concepts, but more emphasis on solving problems that arise in everyday life, practicing their own concept discovery efforts through handling and treating material that is really real. That way students will be more active and easy to understand in the learning process, because the learning model is chosen properly and involves the experiences that students have. With the application of the Experiential Learning learning model in the subject of Automated Management of Facilities and Infrastructure, students become more enthusiastic and enthusiastic in participating in practical learning. One of them is because they have experienced and have their own experiences in their daily lives. Not only in the subject of Automated Management of Facilities and Infrastructure, but also in other subjects. By having their own experience, students become better prepared in solving cases or problems that occur in their daily lives. Students' critical, creative and innovative thinking skills can also be developed in responding to various problems that may occur to them later. In addition, the skills of students are also improved in this case the application of the use of office equipment or supplies (office supplies). With increased skills in the use of office equipment or supplies, of course, skills assessment indicators can be met.